Water Symbolism in John and Martutu Aek: A Biblical-Theological Reading of Religious Literature - Sukanto Limbong; Daniel Razsekar Panjaitan; Sigamoney Shakespeare (Jurnal Lektur Keagamaan, 2026)
This article examines water symbolism in the Gospel of John and the Martutu Aek ritual as two forms of religious literature, namely, a canonical written text and an oral performative ritual text. Previous studies have separately analyzed Johannine water imagery through textual-exegetical lenses and the Martutu Aek through ethnographic-cultural frameworks, leaving largely unexplored the systematic comparison of these traditions through a unified analytical framework. This study aims to compare how water symbolism is constructed and interpreted in both traditions through a biblical-theological and hermeneutic-comparative approach. Employing a qualitative hermeneutical approach, the study analyzes John 3:1–21 and 4:1–42 as primary textual data and scholarly documented ethnographic sources of the Martutu Aek ritual as secondary data, using six structured deductive categories. The findings reveal functional convergences, as both traditions employ water as a sacred medium for rites of initiation, spiritual purification, and the reconstruction of communal identity. A fundamental theological divergence nevertheless emerges: the Johannine narrative directs water symbolism toward an eschatological-transcendental transformation for eternal life, whereas the Martutu Aek ritual emphasizes a restorative-immanent transformation to reestablish socio-cosmic harmony. This article contributes to religious literature studies in the Nusantara by demonstrating how a biblical-theological reading can engage seriously with oral ritual traditions, demonstrating that oral ritual traditions warrant the same analytical rigor as canonical written texts, while also offering implications for contextual theological reflection and ecological awareness in Indonesia.